Acidente vascular cerebral isquêmico direito e suas repercussões em idosos - Gomes, Ana Claudia (2006)
This study has as objective to verify the mental and compartmental state, and elderly subjects functionality and social interaction that underwent a right ischemic cerebral vascular accident (AVCID). The research was accomplished through studying four patients after suffering AVCID, among them, three were women and one man, aged between 60 to 70 years old. The profile of each one was verified and analyzed through an identification questionnaire, then, it was applied other six questionnaires directed to cognitive, compartmental, mood functionality and also social analyses. To accomplish this study, it was used the qualitative and descriptive methodology. This methodology was applied and used to describe and analyze all the studied subject subjectivity. Among the results obtained it was pointed out the motor implication of the left hemi body from all subjects, with damage on its functionality mainly in accomplishing tasks, few cognitive changes, besides affective and social changes. The physiotherapist treatments accomplished by a professional interested and also offer a more consistent psychological support can propitiate motor and functional progress reached faster. However the sequels and physical limitations caused by AVC resound intensively on each elderly subject studied, altering his daily life and his life quality